The Role of Anti-mCRP Autoantibodies in Lupus Nephritis - Mo Yuan; Ying Tan; Ming-hui Zhao (Karger Publishers, 2023)
Background: Lupus nephritis is characterized by multiple autoantibodies production. However, there are few autoantibodies associated with disease activity and prognosis. CRP exists in at least two conformationally distinct forms: native pentameric C-reactive protein (pCRP) and modified/monomeric CRP (mCRP). Autoantibodies against mCRP are prevalent in sera of patients with lupus nephritis and are reported to be pathogenic. Summary: The levels of serum anti-mCRP autoantibodies are associated with clinical disease activity, tubulointerstitial lesions, treatment response, and prognosis in patients with lupus nephritis. The key epitope of mCRP was amino acid 35-47. Furthermore, emerging evidence indicated that anti-mCRP autoantibodies could participate in the pathogenesis of lupus nephritis by forming in situ immune complexes or interfering with the biological functions of mCRP, such as binding to complement C1q and factor H. Key Messages: Here, we review the recent advances in the prevalence, clinical-pathological associations, and potential pathogenesis of anti-mCRP autoantibodies in lupus nephritis, which may provide a promising novel therapeutic strategy for lupus nephritis.